THE ANALYSİS OF RELATİON BETWEEN STOCK RETURNS OF BANKS TRADED IN ISTANBUL STOCK EXCHANGE AND MACRO ECONOMİC FACTORS (Third Sector Social Economic Review, 2010)
In this study, different macro economic factors, which are expected to affect the stock returns of banks traded in İstanbul Stock Exchange, are aimed to be determined. Monthly returns of banks, which are in the banking index and traded in İstanbul Stock Exchange during 2002-2009 period, are examined in the study. The sensitivity of the banks traded in İstanbul Stock Exchange against macro economic factors affecting their stock returns and power of explaining returns are presented.In the study, as macro economic variables, which are expected to affect the banks’ stock returns; exchange rate, repo, treasury bill weighted interest rate, bank index, gross domestic product(GDP), domestic debt and portfolio investment are used. According to the results, there is a negative relation between some of the macro economic factors affecting the equity returns of banks in Turkey; interest rate on deposit, portfolio investment and banking index, while there is a positive meaningful relation with the other explanatory variables.
Keywords: Banking Index; ISE; Macro Economic Variables; Stock Returns; Time Series